1993
DOI: 10.1021/la00032a025
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy studies of polystyrene-poly(methyl methacrylate) core-shell latex particles

Abstract: Poly(methyl methacrylate)-polystyrene (PS-PMMA) core-shell latex particles were prepared by twostage emulsion polymerization under monomer-starved conditions. These particles were examined by three different transmission electron microscopy techniques: cryosectioning, beam damage in ice, and freeze-fracture (FFTEM). This is the first reported application of FFTEM to the study of composite latex morphology. From these experiments we learn that the second stage polymer forms a shell surrounding the seed. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…It seems clear that the large particles are formed in an equilibrium nodular morphology, so the morphology cannot be used to infer anything about mechanism. Thus, there is less mechanistic information available from FFTEM than may have seemed the case to previous investigators (10,11). On the other hand, the small dispersionpolymerized particles were formed in a radial non-equilibrium morphology that could be converted into the nodular morphology by either heating or precipitation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It seems clear that the large particles are formed in an equilibrium nodular morphology, so the morphology cannot be used to infer anything about mechanism. Thus, there is less mechanistic information available from FFTEM than may have seemed the case to previous investigators (10,11). On the other hand, the small dispersionpolymerized particles were formed in a radial non-equilibrium morphology that could be converted into the nodular morphology by either heating or precipitation.…”
Section: Discussionmentioning
confidence: 92%
“…The prior authors applied freeze fracture TEM (FFTEM) to several colloidal particles and concluded that the observed structures implied something about the mechanisms of particle nucleation and growth (10,11). Since our mechanistic study suggested small and large particles grew by different mechanisms, we were anxious to have a look at the freeze fracture morphologies of the polystyrene particles.…”
Section: Growth Stagementioning
confidence: 95%
“…They showed that the seed particles having higher glass transition temperature than the polymerization temperature had an advantage in producing core-shell polymer particles. Shivers et al 40 showed that in the preparation of PS-PMMA core-shell latex particles by two-stage emulsion polymerization, some PS migrates to the surface of the PMMA shell when MMA was polymerized in the presence of PS seed latex. They explained this finding in terms of a combination of thermodynamic and kinetic factors affecting the polymerization and morphology evolution process.…”
Section: Introductionmentioning
confidence: 99%
“…Two-stage emulsion polymerization is a common route for the preparation of core-shell polymer particles. [11][12][13] Using this method, Okubo and Mori 14 prepared different kinds of core-shell polymer particles. Moreover, they developed a dynamic swelling method for the preparation of many multiform core-shell particles.…”
Section: Introductionmentioning
confidence: 99%